Application of the GIS modeling technique and weights-of-evidence method for prospecting tungsten minerals in the Pleimeo area, Kontum province - An, Đỗ Mạnh; Bắc, Bùi Hoàng; Dũng, Nguyễn Tiến; Hùng, Khương Thế; Mạnh, Trương Hữu; Hưng, Nguyễn Duy (Vietnam Journal of Earth Sciences, 2013)
The Pleimeo area, Kontum province, has a high potential for valuable minerals including tungsten. However, mineral investigation in this area is still limited because of difficult topographical and transportation conditions and distance from residential area. In order to overcome those obstacles, authors introduce the application of the GIS modeling combining with a geomathematic method for prospecting tungsten mineral in the Pleimeo area. Based on synthesized and analytic geological data related to tungsten (petrological, structural, geochemical, and geophysical map), a database in GIS environment was generated and analyzed by using weight of evidence method.Buffer zones were created along lineaments with intervals of 100 ÷ 500 m and the optimal spatial evidences related to tungsten mineral in the area were also determined. Eight evidences that satisfy the independent conditions were used to create a potential tungsten mineral map in Pleimeo area. Three zones with different levels of high potential, potentialand low potential were identified. These results can be used as guidelines for future mineral exploration in the area.